Catholic, apostolic, and orthodox - Haldane, John (New blackfriars, 2025)
Commentary on the election of Pope Leo XIV has been framed in terms drawn from political and cultural oppositions: conservative vs liberal, traditionalist vs progressive, made vivid by the 2024 film Conclave based on Robert Harris’s 2016 novel. Part of my concern is to urge rejection of these as general terms of analysis of Catholicism, or at least to circumscribe their applications to matters inessential to Catholic faith and morals per se. In aid of that, and by way of broader purpose, I discuss the nature of Catholicism itself. Observing the long history of challenges, crises, and divisions, I then proceed to distinguish between subjective and objective modes of identifying the nature of individuals and institutions. Catholicism has a robust objective nature comprising a synthesis of Hebrew and Christian scripture, apostolic tradition, conciliar and other authoritative teachings, and sacramental practices, together consolidated and expressed in orthodoxy and orthopraxy. Political and cultural classifications are irrelevant to and distracting from this identification.